Respon Pembaca Terhadap Teks Channel At The Bottom Of The Sea Karya Stephanie Ye Mengenai Pemahaman Komunikasi Interkultural - Sherien Sabbah; Thafhan Muwaffaq; Lusi Lian Piantari (Universitas Al Azhar Indonesia, 2023)
This research examines students’ understanding of intercultural communication issues through text reading using a short story entitled Channel at the Bottom of the Sea written by a Singaporean author, Stephanie Ye. A readers’ response qualitative method is used in conducting this research which uses a literary text focusing on multicultural themes. By using Martin and Nakayama’s intercultural communication concepts specifically on the four barriers in intercultural communication, this analysis examines 25 students’ response in understanding, reacting, and reflecting intercultural communication cases. In conclusion, it can be seen that 64% students responded well enough in perceiving the issues of intercultural communication in a multicultural context. Key Word: Intercultural Communication, Literary Text, Multiculturalism, Readers’ Response, Stephanie Ye.